Book Review: Rural Education: Issues and Practices - Jaqueline D. Spears (Journal of Research in Rural Education, 1993)
Part of a series of source books in education Rural Education: Issues and Practice is a collection of essays that introduces a reader to both the issues and the scholarly work of the field. In the editor's words, flit is my hope that each of the chapters to follow will spur readers to continue their readings in each content area" (p. xvii). For thisreader, the editor's hope was realized. I found the essays to be interesting, well-written, and stocked with an abundance of references for further reading.